Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2196/mededu.7587
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Lifestyle Medicine Curriculum: Facilitating Education About Lifestyle Medicine, Behavioral Change, and Health Care Outcomes

Abstract: BackgroundLifestyle medicine is the science and application of healthy lifestyles as interventions for the prevention and treatment of disease, and has gained significant momentum as a specialty in recent years. College is a critical time for maintenance and acquisition of healthy habits. Longer-term, more intensive web-based and in-person lifestyle medicine interventions can have a positive effect. Students who are exposed to components of lifestyle medicine in their education have improvements in their healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
(45 reference statements)
0
5
0
4
Order By: Relevance
“…The World Health Organization (WHO) reported that the incidence rate of chronic disease is not only related to social and economic factors but also to individuals’ eating habits and physical activities such as drinking and smoking [ 9 ]. Sedentary lifestyle, high-calorie diet, sweetened drinks, low economic status, and saturated fats are key risk factors that increase the risk of obesity; however, regular physical activity is known to lower individuals’ risk [ 10 , 11 ]. People who are habitually active, less sedentary, and have better cardio-pulmonary functions are less obese and thus have lower incidence rates of MetS [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization (WHO) reported that the incidence rate of chronic disease is not only related to social and economic factors but also to individuals’ eating habits and physical activities such as drinking and smoking [ 9 ]. Sedentary lifestyle, high-calorie diet, sweetened drinks, low economic status, and saturated fats are key risk factors that increase the risk of obesity; however, regular physical activity is known to lower individuals’ risk [ 10 , 11 ]. People who are habitually active, less sedentary, and have better cardio-pulmonary functions are less obese and thus have lower incidence rates of MetS [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, appropriate prevention and intervention is needed in all related fields [ 14 ]. One can significantly lower the risk of and prevent MetS by controlling diet habits, physical activity, smoking, drinking, and stress levels [ 10 , 15 , 16 ]. In particular, men aged 30 to 39 years and women aged 20 to 29 years have worse health activity compared to other age categories, and thus require more active and focused health management to improve their health habits and prevent chronic diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…59 Frates ve ark. 60 hazırladığı web tabanlı YTT dönemlik dersi, öğrencilerin fiziksel aktivite, beslenme, uyku, stres konularında kanıta dayalı rehberleri kullanarak yaşam tarzı koçluk ve danışmanlığı yapabilmelerini hedeflemiştir. Çoğunluğunu lisans ve yüksek lisans öğrencilerinin oluşturduğu farklı disiplinlerden katılımcılar tarafından üç yılda dersin kabul edilebilirlik ve seçim puan ortalamaları 4,9 (max:5) olarak belirlenmiştir.…”
Section: Sağlıklı Yaşam Tarzı: Neredeyiz?unclassified
“…Çoğunluğunu lisans ve yüksek lisans öğrencilerinin oluşturduğu farklı disiplinlerden katılımcılar tarafından üç yılda dersin kabul edilebilirlik ve seçim puan ortalamaları 4,9 (max:5) olarak belirlenmiştir. 60 Eğitim çalışmaları lisans, lisansüstü ve tıpta uzmanlık öğrencileri gibi farklı seviyelerden öğrenciler ile yapılmış bunun yanı sıra interdisipliner sağlık ekibine yönelik hazırlanan kurs program değerlendirme çalışmaları da mevcuttur. Dacey ve ark.…”
Section: Sağlıklı Yaşam Tarzı: Neredeyiz?unclassified
See 1 more Smart Citation